Expression pattern and regulation of genes differ between fibroblasts of adhesion and normal human peritoneum - Saed Ghassan M; Rout Ujjwal K; Diamond Michael P (BMC, 2005)
Abstract Background Injury to the peritoneum during surgery is followed by a healing process that frequently results in the attachment of adjacent organs by a fibrous mass, referred commonly as adhesions. Because injuries to the peritoneum during surgery are inevitable, it is imperative that we understand the mechanisms of adhesion formation to prevent its occurrence. This requires thorough understanding of the molecular sequence that results in the attachment of injured peritoneum and the development of fibrous tissue. Recent data show that fibroblasts from the injured peritoneum may play a critical role in the formation of adhesion tissues. Therefore, identifying changes in gene expression pattern in the peritoneal fibroblasts during the process may provide clues to the mechanisms by which adhesion develop. Methods In this study, we compared expression patterns of larger number of genes in the fibroblasts isolated from adhesion and normal human peritoneum using gene filters. Contributions of TGF-beta1 and hypoxia in the altered expression of specific genes were also examined using a semiquantitative RT-PCR technique. Results Results show that several genes are differentially expressed between fibroblasts of normal and adhesion peritoneum and that the peritoneal fibroblast may acquire a different phenotype during adhesion formation. Genes that are differentially expressed between normal and adhesion fibroblasts encode molecules involved in cell adhesion, proliferation, differentiation, migration and factors regulating cytokines, transcription, translation and protein/vesicle trafficking. Conclusions Our data substantiate that adhesion formation is a multigenic phenomenon and not all changes in gene expression pattern between normal and adhesion fibroblasts are the function of TGF-beta1 and hypoxia that are known to influence adhesion formation. Analysis of the gene expression data in the perspective of known functions of genes connote to additional targets that may be manipulated to inhibit adhesion development.